The impact of community works programme on poverty alleviation at Erasmus Village in the City of Tshwane Metropolitan Municipality of Gauteng Province - Hlongo, Nganyane Ernes (My University, 2023)
The primary objective of the Community Works Programme (CWP) is to provide a safety net to the poor, unemployed and under-employed people by providing them with regular and predictable work opportunities enabling them to earn a monthly wage (DCoG, 2017). CWP was established as a government-wide initiative targeting the poorest wards in each area of implementation. The study investigated its impact on poverty-alleviation among participants at Erasmus village of the City of Tshwane Metropolitan Municipality in Gauteng province. A multiple data collection approach was used to collect data. Quantative data approach was collected with 81 respondents whilst qualitative data was collected among programme administrators through focus group interview. Simple random sampling was used to sample respondents whilst a questionnaire was administered in data collection. The collected data was processed using MS Excel system with results presented in tables and graphs. The study found a relationship on impact among public employment programme implemented in south Africa i.e. EPW and CWP. In both programmes, the stipend was used to purchase family basic goods and service, payment of school fees, community psychosocial needs such as payment of burial societies, Stokvel and to some extent, payment of municipal services. The activities undertaken by participants using income earned from the programme were found to have presented an opportunity for local economic growth in the community. This includes increased spending on local goods such as taxi fare, local garden vegetables and purchasing of locally made school uniform. The skills acquired by participants in the programme include both generic and technical. The basic nature of skills acquired were found to be incapable of assisting participants to find new jobs or exit the programme to form their own businesses. The skills provided in the programme since the programme started in 2007 require a review, both in terms of courses offered and alignment with the modern economy needs.
Thesis (M.Dev. (Planning and Management)) -- University of Limpopo, 2023
Keywords: Community Works Programme; Poverty-alleviation; Sustainable livelihoods.; Poverty -- South Africa -- Gauteng -- Prevention; Community development -- South Africa -- Gauteng; Sustainable development -- South Africa -- Gauteng